Virtual water and water footprints offer limited insight regarding important policy questions - Wichelns, Dennis (Informa UK Limited, 2010)
Much of the literature regarding virtual water and water footprints focuses on the potential water savings that might be realized when water-short countries import water-intensive agricultural goods from countries with larger water endowments. Some of the published estimates of potential national and global water savings made possible through international trade are quite large and they do not reflect actual or potential opportunities to save water. Recent additions to the virtual water literature describe the pressure placed on water resources in one country by consumers of imported products in another. Some authors suggest that, through international trade, consumers are partly responsible for water resource problems in distant regions. Although one goal of virtual water analysis is to describe opportunities for improving water security, there is almost no mention of the potential impacts of the prescriptions arising from that analysis on farm households in industrialized or developing countries. It is essential to consider more carefully the inherent flaws in the virtual water and water footprint perspectives, particularly when seeking guidance regarding policy decisions.